Weaved piezoresistive triboelectric nanogenerator for human motion monitoring and gesture recognition. (1st June 2022) - Yan, Lixia; Mi, Yajun; Lu, Yin; Qin, Qinghao; Wang, Xueqing; Meng, Jiajing; Liu, Fei; Wang, Ning; Cao, Xia
Abstract: Self-powered tactile sensors based on triboelectric nanogenerators (TENGs) can be sustainable and intelligent for dynamically monitoring various physiological signals and motions. Nevertheless, it is still very challenging for the TENG-based sensors to be simultaneously sensitive to deformation caused by stress and strain. Herein, a piezoresistive fiber-base triboelectric sensor (PRF-TES) is designed by using nylon thread, silver nanowires (Ag NWs), carbon nanotubes (CNTs), Parafilm and polydimethylsiloxane (PDMS) as source materials. The elaborate hierarchical structure of the textile PRF-TES ranges from one-dimensional macroscopic fibers to elastic polymer with an internal nanoscale CNTs percolation network, which presents a relatively large contact area, multiple contact points and large deformation space for both mechanical energy collection and force sensing. Dynamically, the textile TENG enables the monitoring of physically changes of human body (for example, joint movement, gesture, etc.), but also the information on the contacted object, such as material texture, type and shape. Statically, it can sensitively detect the stress and strain itself as well as the mass and position of the touched object in the two-dimensional space. This work enlightens the development of highly sensitive and multimodal sensors for broad application in personal health monitoring and human-computer interaction. Graphical Abstract: ga1 A piezoresistive fiber-base triboelectric tactile sensor coupled with triboelectric and piezoresistive effects is demonstrated, which can be used as a textile TENG to dynamically monitor the physical changes of the human body and the information of contact objects. This tactile sensor device can also act as a piezoresistive sensor, sensitively detecting stress, strain, and the weight and position of the object being touched in two-dimensional space. This technology has broad application prospects in wearable energy acquisition and sensing. Highlights: Weaved triboelectric nanogenerator (PRF-TES) was fabricated with stretchable piezoresistive coaxial fibers. Good air permeability, comfort and wearability were achieved. Triboelectric and piezoresistive effects were coupled for self-powered multimodal force sensing. Environmental stimuli such as dynamic and static forces, as well as the corresponding position, can be simultaneous detected, promoting their further application in motion monitoring and gesture recognition.